ETHNOMATHEMATICS OF 100-PILLARS LIMAS HOUSE AND ITS INTEGRATION IN MATHEMATICS LEARNING FOR JUNIOR HIGH SCHOOL - Nur Aziza; Somakim Somakim; Budi Mulyono (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The purpose of this study is to explore ethnomathematicss elements in 100-Pillars Limas House and integrate it into mathematic learning. This research use ethnographic approach. The data are collected through interviews, observation, documentation, and test. The data obtained from observations and interviews are carried out by data analysis with the stages of data reduction, data display and verification. While the data obtained from the test will be analyzed by accumulating the test results of students who reach the KKM and then looking at the completeness of student learning outcomes. The results of this study indicate that: (1) there are several mathematical concepts, namely geometry and symmetry used in the construction of the 100-pillars Limas house structure and the philosophy that underlies each of the parts contained in the house. 2) its integration in learning mathematics is conducted to contextualize abstract mathematical objects so that the student will be easier to understanding mathematical concepts while introducing cultural elements to students. The learning outcomes of students after implementing ethnomathematicss-based learning shows that there are 88% of students who finished the integration of ethnomathematicss into mathematic learning in effective category.